Effect of separation mechanism on the kinetics of Zn(II) flotation. Issue 17 (22nd November 2018) - Hoseinian, Fatemeh Sadat; Rezai, Bahram; Kowsari, Elaheh
ABSTRACT: In this study, the kinetics study and separation mechanism of zinc ion removal from synthetic wastewater were investigated using the foam separation process. With increasing the pH, Zn(II) recovery increased, in which foam fractionation occurred at pH 1.5, 3 and 5.5 and ion flotation at pH 8. The kinetics study was also used to determine separation mechanism. The order of Zn(II) foam fractionation was n = 1, while the order of Zn(II) ion flotation was n = 2 at the first stage and n = 0 at the second stage. Water recovery kinetics also increased with increasing ionic strength.